Exploring the targetome of IsrR, an iron-regulated sRNA controlling the synthesis of iron-containing proteins in Staphylococcus aureus - Ganske, Alexander; Busch, Larissa Milena; Hentschker, Christian; Reder, Alexander; Michalik, Stephan; Surmann, Kristin; Völker, Uwe; Mäder, Ulrike (Frontiers in Microbiology, 2024)
Staphylococcus aureus is a common colonizer of the skin and nares of healthy individuals, but also a major cause of severe human infections. During interaction with the host, pathogenic bacteria must adapt to a variety of adverse conditions including nutrient deprivation. In particular, they encounter severe iron limitation in the mammalian host through iron sequestration by haptoglobin and ironbinding proteins, a phenomenon called "nutritional immunity". In most bacteria, including S. aureus, the ferric uptake regulator (Fur) is the key regulator of iron homeostasis, which primarily acts as a transcriptional repressor of genes encoding iron acquisition systems. Moreover, Fur can control the expression of trans-acting small regulatory RNAs that play an important role in the cellular iron-sparing response involving major changes in cellular metabolism under iron-limiting conditions. In S. aureus, the sRNA IsrR is controlled by Fur, and most of its predicted targets are iron-containing proteins and other proteins related to iron metabolism and iron-dependent pathways. To characterize the IsrR targetome on a genome-wide scale, we combined proteomics-based identification of potential IsrR targets using S. aureus strains either lacking or constitutively expressing IsrR with an in silico target prediction approach, thereby suggesting 21 IsrR targets, of which 19 were negatively affected by IsrR based on the observed protein patterns. These included several Fe-S cluster-and heme-containing proteins, such as TCA cycle enzymes and catalase encoded by katA. IsrR affects multiple metabolic pathways connected to the TCA cycle as well as the oxidative stress response of S. aureus and links the iron limitation response to metabolic remodeling. In contrast to the majority of target mRNAs, the IsrR-katA mRNA interaction is predicted upstream of the ribosome binding site, and further experiments including mRNA half-life measurements demonstrated that IsrR, in addition to inhibiting translation initiation, can downregulate target protein levels by affecting mRNA stability.